2022
DOI: 10.1186/s12909-022-03315-9
|View full text |Cite
|
Sign up to set email alerts
|

Learning the ropes: strategies program directors use to facilitate organizational socialization of newcomer residents, a qualitative study

Abstract: Background Many residents experience their transitions, such as from medical student to resident, as demanding and stressful. The challenges they face are twofold: coping with changes in tasks or responsibilities and performing (new) social roles. This process of ‘learning the ropes’ is known as Organizational Socialization (OS). Although there is substantial literature on transitions from the perspective of residents, the voices of program directors (PDs) who facilitate and guide residents thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Both groups could consider responding to each other's needs and interests by adapting their strategies to individual preferences. 23 Practical implications practical implications logically follow from the results of our study. First, we recommend to incorporate information about individual adaptation strategies into onboarding programs for residents.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Both groups could consider responding to each other's needs and interests by adapting their strategies to individual preferences. 23 Practical implications practical implications logically follow from the results of our study. First, we recommend to incorporate information about individual adaptation strategies into onboarding programs for residents.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, program directors did not identify absence of a role model as a strategy they could use. 23 To our knowledge, other studies did not address absence of a role model, but instead they showed the tension between support and autonomy. 2,60,61 Residents' responsibilities did not always match their desired degree of autonomy, but were perceived as either too excessive or too limited.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Newcomers may learn role expectations from their supervisors via knowledge and feedback (Ostroff and Kozlowski, 1992). Also, supervisors serve as role models for newcomers (Galema et al , 2022; Holton and Russell, 1997; Weiss, 1977), as well as define proper role behaviors, and can provide more and accurate information about newcomers’ positions than can coworkers (Graen, 1976; Schein, 1988). Based on Graen’s (1976) interpersonal role-making model, supervisors also have official power in newcomers’ role negotiations.…”
Section: Supervisors’ Roles In Newcomer Organizational Socializationmentioning
confidence: 99%